Human Effects in Holocene Fire Dynamics of Central Western Patagonia ( 44° S, Chile) - Méndez, César; de Porras, María E.; Maldonado, Antonio; Reyes, Omar; Nuevo Delaunay, Amalia; García, Juan-Luis (Frontiers in Ecology and Evolution, 2016)
The forest-steppe ecotone of the eastern slope of the Andes in Central Western Patagonia (43°40'-49°15' S, Chile, South America) provides a unique area for assessing long and short term dynamics between humans and past environments. Central Western Patagonian was a demographically marginal zone inhabited intermittently and with low intensity by hunter-gatherers during the Holocene. This paper adopts a novel approach in order to assess the relationship between trends in the archaeological, pollen and charcoal records. The recognition of temporal and spatial scales in both archaeology and paleoecology is crucial for defining roles in paleofire records. The main goal of the paper is to assess the role of climate and human beings as potential ignitors of wildfires by acknowledging the scales in which they operate and the different roles either one played in paleofire trends. We investigated a case study in the Cisnes River Valley where the frequencies and magnitudes of fire episodes – reconstructed from macro-charcoal particles from the Lake Shaman intermoraine sequence – can be attributed to human action, while acknowledging the driving role of climate over broader time scales. The Lake Shaman charcoal record spanning the last 19000 cal years is compared to the archaeological record starting at 11500 cal years BP. After comparing paleofires, reconstructed from the charcoal record, with peaks and troughs in the radiocarbon record and archaeological evidence at local and site scales, we argue that this approach provides insights for assessing the timing and magnitude of human effects on the environment. We examine collation and correlation scenarios for comparative trends between the archaeological, pollen and charcoal records. The correlation of occupational events at the El Chueco 1 archaeological site and other sites along the Cisnes River Valley with the results obtained at Lake Shaman is suggestive of a combination of human agency and climate drivers in the occurrence of fires during most of the Holocene.